669Rheumatic Heart Disease outcomes in Australia: a linked data analysis. (2nd September 2021) - Stacey, Ingrid; Bond-Smith, Daniela; Seth, Rebecca; Cannon, Jeffrey; Murray, Kevin; Ralph, Anna; Carapetis, Jonathan; Hung, Joe; Katzenellenbogen, Judith
Abstract: Background: Rheumatic Heart Disease (RHD), a chronic acquired heart-valve disease, is a major contributor to morbidity and mortality among Indigenous Australians. We estimate the probability and determinants of progressing from RHD diagnosis to cardiovascular complications/death in the Australian population, addressing methodological shortcomings in existing evidence. Methods: This retrospective cohort study used linked RHD register, hospital and death data from five Australian jurisdictions. Cardiovascular complications (heart failure, stroke, endocarditis, atrial fibrillation) and all-cause mortality were measured for people aged <35years diagnosed with first-ever RHD (2010-2018; minimum 8.5year look-back; maximum 8year follow-up). Probability of cardiovascular complications were determined with competing risk of death. Proportional cause-specific hazard regression measured independent predictors of outcomes. Results: 1718 RHD cases aged <35years were identified (85% Indigenous, 11% migrant, 63% women, 40% 5-14years, 16% metropolitan). Within 8years, 22% experienced a cardiovascular complication (50% heart failure) and 3.2% died. Age ≥14years (Hazard Ratio, HR:2.0, 95% Confidence Interval, CI:1.4-3.0) and metropolitan residence (HR:3.2, 95%CI:2.0-5.1) were associated with increased risk of cardiovascular complications in cases (relative to < 14years and non-metropolitan). Record of ARF prior to RHD was protective (HR:0.6, 95%CI:0.4-0.8). Conclusions: Competing risks methods applied to linked data have provided the most comprehensive multi-jurisdictional estimates of RHD progression to cardiovascular complications/death in Australia. Risk of cardiovascular events was highest in metropolitan areas but clinical history of ARF was associated with reduced risk of progression. Key messages: Despite access to the world-class Australian healthcare system, one-fifth of initially uncomplicated RHD diagnoses will progress to one of the complications examined within 8years